Ponto de luz: a configuração de identidades através de um produto midiático - Mônego, Jozéli da Rosa (2010)
His dissertation proposes to examine the general characteristics of religiosity in contemporary Brazil. Contextualizing the role of media such as churches, in particular neopentecostais seeks to understand its prosperous growth, opposite to the characteristics of current society. With this objective, examines the media strategies employed by these religious institutions, in our case, the Universal Church of the Kingdom of God (IURD), to question its faithful, which involves the construction of identity itself IURD through its agents , its faithful and those who believe in potential, that the media call. Thus, examining in particular a television program, Point of light.